(untitled) (Research, Society and Development, 2025)
The objective of this study is to report on the humanized approach to welcoming as a way to help patients overcome fear, transforming it into trust and adherence to treatment in a family clinic. An experience report study was carried out. The study focused on reporting the use of techniques proven in the literature for pain management and control of anxious behaviors in patients with a history of objective or subjective fear or trauma from previous procedures. The contribution of these strategies has an impact on improving the patient-dentist bond, on the teaching-learning process of the student and future professional in a clinical environment, promoting a more sensitive and effective performance in comprehensive care and a multidisciplinary approach. And also, in the humanized approach as central tools in oral health care. Thus, revealing the importance of care as an essential tool in the construction of a more resolutive, ethical and humanized care model, focusing on overcoming dental fear and promoting adherence to treatment by users. Therefore, care is a fundamental instrument in transforming the dental experience, strengthening trust, continuity of care and comprehensive health education.